Effect of Gd infiltration on NiO-CeO2 anode substrates for intermediate-temperature solid oxide fuel cells. Issue 12 (15th August 2017) - Jang, Inyoung; Kim, Chanho; Kim, Sungmin; Yoon, Heesung
Abstract: In this study, solid oxide fuel cells (SOFCs) were fabricated using cerium oxide in the anode support layer (ASL) instead of gadolinium-doped ceria (GDC). To compensate for the deficiency in ionic conductivity and catalytic activity of CeO2, a gadolinium nitrate solution was infiltrated in the ASL before sintering at 1450 °C. The ohmic and polarization resistance of the cell were reduced upon Gd-nitrate infiltration, which also increased the sinterability of the ASL. However, excessive infiltration was found to degrade the electrochemical properties of the cell. Therefore, the conditions for infiltration were optimized in this study. The peak power density of the cell after Gd-nitrate infiltration was 0.662 W, 68% higher than that of the reference cell without Gd-nitrate infiltration.